New advances in the treatment of endometrial cancer. (March 2011) - Roque, Dario R; Dizon, Don S
Endometrial carcinoma is the most common gynecological malignancy. Prognosis is poor following disease recurrence or diagnosis at an advanced stage. In this setting, combination chemotherapy is the hallmark of therapy. However, women who develop recurrence or metastatic disease after initial treatment have limited options for additional therapy. This emphasizes the need for new treatment approaches, many of which are currently under investigation. A literature review was performed to determine current and future treatment options for endometrial cancer. The epothilones, angiogenesis inhibitors and mTOR inhibitors are three emerging second-line agents with promising activity against endometrial cancer. Clinical trials are underway to determine how to best incorporate emerging therapies in the treatment of endometrial carcinoma.